1996
DOI: 10.1007/bf00019559
|View full text |Cite
|
Sign up to set email alerts
|

A gene for Brassica napus extensin is differentially expressed on wounding

Abstract: We have analysed the expression of the endogenous extensin genes in Brassica napus, using northern hybridisation and dot blotting. In the unstressed plant, the extA gene is only expressed in the root, expression in the leaf, petiole and stem being absent. We have found that wounding dramatically alters this normal pattern of expression. Expression in wounded leaf is seen after 36 h, in wounded petioles after 11 h and in wounded stem after 17 h. Differences in the amount of extensin mRNA accumulated are also se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
2
12
0
Order By: Relevance
“…No staining was detected in the tissues of the internodal regions. Similar findings had also been reported by Shirsat et al (1996) who detected expression of the extA::GUS fusion gene in the internal and external phloem and in the cortical parenchyma in transgenic tobacco at the regions where the auxiliary stalk was developed. In another study, GUS staining localised expression of the tobacco Ext1.4::GUS fusion gene to the internal and external phloem at stem nodes and also in the floral pedicels (Hirsinger et al, 1999;Salvá and Jamet, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No staining was detected in the tissues of the internodal regions. Similar findings had also been reported by Shirsat et al (1996) who detected expression of the extA::GUS fusion gene in the internal and external phloem and in the cortical parenchyma in transgenic tobacco at the regions where the auxiliary stalk was developed. In another study, GUS staining localised expression of the tobacco Ext1.4::GUS fusion gene to the internal and external phloem at stem nodes and also in the floral pedicels (Hirsinger et al, 1999;Salvá and Jamet, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…This detailed analysis consisted of observing successive sections of the transgenic plants, practising our belief that expression analysis should be performed in a very thorough manner in order to detect potential differences among the various tissues. In addition, our study enables the direct comparison of the expression patterns of the various extensin gene family members in tobacco, a widely used experimental system to analyse the developmental and stress-induced expression of many extensin genes in the past (Tire et al, 1994;Wycoff et al, 1995;Ahn et al, 1996;Shirsat et al, 1991Shirsat et al, , 1996Hirsinger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Extensin expression in response to applied stress conditions, such as wounding (Ludevid et al 1990;De Loose et al 1991;Adams et al 1992;Bown et al 1993;Parmentier et al 1995;Wycoff et al 1995;Ahn et al 1996;Hirsinger et al 1997Hirsinger et al , 1999, pathogen infection (Corbin et al 1987;Memelink et al 1993;Niebel et al 1993;Tire´et al 1994;Hirsinger et al 1997) and treatment with compounds known to be involved in various plant defense responses (Ecker and Davis 1987;Tagu et al 1992;Memelink et al 1993;Shirsat et al 1996b;Ahn et al 1996;Hirsinger et al 1999;Merkouropoulos et al 1999) supports a role for extensins in plant defense. Increased extensin deposition and extensin cross-linking has been proposed to assist in wound healing and also in the formation of a physical barrier against invading pathogens, thereby preventing the entry of pathogens into the vascular system and therefore limiting systemic pathogen spread (Showalter 1993).…”
Section: Introductionmentioning
confidence: 84%
“…However, very few studies have demonstrated the deposition of specific HRGPs as part of the plant defense. Several studies have described increased expression of specific extensin genes in response to elicitation, plant-pathogen interaction, wounding, or other stress (Showalter et al, 1991;Kawalleck et al, 1995;Parmentier et al, 1995;Shirsat et al, 1996;Hirsinger et al, 1997). However, it is unclear from such studies whether the extensin genes expressed during plant defense are involved in modifying the covalent cell wall structure because extensin deposition was not shown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is overwhelming evidence supporting a major role for extensin deposition in the later, transcription-dependent response to pathogens, elicitors, and wounding (Showalter, 1993). Molecular studies have demonstrated repeatedly increased expression of extensin mRNA in defensive responses (Memelink et al, 1993;Shirsat et al, 1996).…”
mentioning
confidence: 99%